PRMT1 expression in renal cell tumors- application in differential diagnosis and prognostic relevance - Jelena Filipović; Martina Bosić; Sanja Ćirović; Maja Životić; Duško Dunđerović; Dejan Đorđević; Snežana Živković-Perišić; Aleksandar Lipkovski; Jasmina Marković-Lipkovski (BMC, 2019)
Abstract Background Protein arginine methyltransferase-1 (PRMT1) is associated with the progression of various tumor types and the process of epithelial to mesenchymal transition (EMT). However, the expression of PRMT1 in renal cell tumors (RCT) is unknown. Methods We evaluated PRMT1 immunohistochemical (IHC) expression on tissue microarray (TMA) of 208 specimens of RCT, including clear cell renal cell carcinomas (ccRCC), papillary RCC type I and II (pRCC I and II), chromophobe RCC (chRCC), renal oncocytomas (RO), collecting duct carcinomas - Bellini (CDC) and multilocular cystic renal cell neoplasms of low malignant potential (MLCRN-LMP). Moreover, a subset of ccRCC, pRCC, chRCC, RO were also studied using conventional sections. PRMT1 expression in tumor tissue was compared to the IHC expression of EMT-related transcription factors (ZEB1, RUNX1, and TWIST1) and cell surface markers (ß-catenin, N- and E-cadherin). Additionally, qRT-PCR expression of PRMT1 in ccRCC, pRCC, and chRCC was evaluated and the results were compared to the mRNA PRMT1 transcript profiling data in The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) cohort. Results PRMT1 immunoreactivity was observed in the majority of ccRCC, RO, all MLCRN-LMP, but in a minority of chRCC (p = 0.044), and it was associated with low grade and low stage ccRCC (p = 0.014; p = 0.044, respectively). ZEB1 immunoreactivity was noted in all RO, in minority of chRCC and neither of MLCRN-LMP (p < 0.001). The majority of PRMT1-negative ccRCC was negative to ZEB1 and showed cytoplasmic expression of TWIST1 (p = 0.028; p < 0.001, respectively). PRMT1 positive ccRCC mostly expressed RUNX1 (p = 0.019). PRMT1 and ZEB1 expression were associated with better cancer-specific survival in patients with ccRCC (p = 0.029; p = 0.009, respectively). In multivariate analysis, ZEB1 expression was an independent prognostic factor for cancer-specific survival (hazard ratio [HR], 0.367; p = 0.026). Significant IHC heterogeneity was observed in PRMT1, ZEB1 and TWIST1 expression (p < 0.001). Homogenous loss of PRMT1 was associated with high grade and high stage ccRCC, while the homogenous loss of PRMT1 and ZEB1 was more frequent in patients who died of ccRCC (p = 0.017; p = 0.040; p = 0.044; p = 0.009, respectively). Relative mRNA-PRMT1 expression in both cohorts was down-regulated in tumor tissue compared to non-tumor parenchyma (p = 0.009). Unlike in our samples, mRNA-PRMT1 expression in the TCGA cohort was not correlated to ccRCC tumor stage or grade. PRMT1, ZEB1, and TWIST1 expression were not associated with EMT related aberrant ß-catenin expression, a gain of N-cadherin or loss of E-cadherin expression. Only RUNX1 was associated with a gain of N-cadherin (p = 0.003). Conclusions IHC expression of PRMT1 may be characteristic for low grade and low stage ccRCC, while the homogenous loss of PRMT1 may be significant for high grade and high stage ccRCC. Both, PRMT1 and/or ZEB1 expression, could be associated with better survival of the patients with ccRCC.